2020
DOI: 10.2196/16365
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gamification and Oral Self-Care on Oral Hygiene in Children: Systematic Search in App Stores and Evaluation of Apps

Abstract: Background Poor oral hygiene is a great public health problem worldwide. Oral health care education is a public health priority as the maintenance of oral hygiene is integral to overall health. Maintaining optimal oral hygiene among children is challenging and can be supported by using relevant motivational approaches. Objective The pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 63 publications
0
24
0
4
Order By: Relevance
“…In 2018, one-third of the world’s population had smartphones [ 2 ]. The increasing use of smartphones led to explosive growth in usage of smartphone applications (apps) aiming to promote the health status and hygienic behaviors, In 2019, a systematic search in app stores found 612 apps related to oral health [ 3 ]. Another systematic review showed that Mobile-health strategies could work as additional tool for enhancing oneself oral hygiene, in particular to manage gingivitis, and to improve oral health knowledge [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, one-third of the world’s population had smartphones [ 2 ]. The increasing use of smartphones led to explosive growth in usage of smartphone applications (apps) aiming to promote the health status and hygienic behaviors, In 2019, a systematic search in app stores found 612 apps related to oral health [ 3 ]. Another systematic review showed that Mobile-health strategies could work as additional tool for enhancing oneself oral hygiene, in particular to manage gingivitis, and to improve oral health knowledge [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of apps was evaluated using a standardized methodology, including the uMARS tool, and the overall uMARS app quality score was 3.66 (SD = 0.65), which is considered as a moderate overall quality in comparison to the other studies [42][43][44][45][46]. Overall, 33.3% (n = 11) of the apps were developed by small or medium-sized enterprises, 6.1% (n = 2) by healthcare-related agencies, and 3% (n = 1) by an educational organization (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a systematic search of commercially available apps using a rigorous methodology that has been previously published [33,34]. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist [35] is available in Multimedia Appendix 1.…”
Section: Searching Screening and Reviewing Of Commercially Available Appsmentioning
confidence: 99%
“…The total score for the SUS is 100 points, which is divided into six usability categories including worst imaginable (0-25 SUS score), poor (25.1-51.6 SUS score), ok (51.7-62.6 SUS score), good (62.7-72.5 SUS score), excellent (72.6-84.0 SUS score), and best imaginable (84.1-100 SUS score) [42][43][44]. The uMARS and SUS have been used in similar studies [31,32,34,[45][46][47].…”
Section: Rating Tools For App Quality and Usabilitymentioning
confidence: 99%